2021
DOI: 10.1007/s12126-021-09467-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment and Guidance for Ageing Urban Women

Abstract: The number of older women are increasing more rapidly and it is estimated that by 2050, the number of elderly women over 60 years old will be 3.2 times that of 2000. Moreover, the number and rate of elderly women in cities where widowed life alone has increased. The study pays attention to the fragile and vulnerable group of urban elderly women. Hence, the purpose of the study to suggest psychological adjustment and guidance for ageing urban women. The study suggests that by adopting protective policies and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…With time, they have further shifted their attention to seeking remedies for diseases as well [ 49 , 50 ]. According to the United Nations estimation, there are 703 million people over the age of 65 by 2019 globally, which is predicted to reach 1.5 billion by 2050 [ 51 ]. Parallelly, the increase in the elderly population has resulted in 50 million cases of dementia worldwide, which might reach 130 million cases by 2050 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…With time, they have further shifted their attention to seeking remedies for diseases as well [ 49 , 50 ]. According to the United Nations estimation, there are 703 million people over the age of 65 by 2019 globally, which is predicted to reach 1.5 billion by 2050 [ 51 ]. Parallelly, the increase in the elderly population has resulted in 50 million cases of dementia worldwide, which might reach 130 million cases by 2050 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The person can generate more favorable judgments about herself and her abilities and increase her resilience in facing difficulties and misfortunes with more strict feedback and strategies under stressful situations [26]. Promoting psychological capital in the increasing population of widowed women can help this group experience a healthier and happier life [27]. Studies by Vahidian et al [28] and Vale et al [29] reported increased psychological capital after the training intervention, respectively, in the group of female nurses and female teachers, which is congruent with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A quarter of the world's population is projected to be 65 or older by mid-century. [39] Figure 3 shows that developing regions have a much faster rate of aging population growth than developed regions. Because of this, the world's older population is growing in developing regions.…”
Section: Impact Of Climate Change On Aging Health In Developing Count...mentioning
confidence: 99%